A critical literature review on the washback effect of task-based vocabulary assessment on Iranian EFL learners - Fasih, Parima (Frontiers in Education, 2022)
The present critical literature review explored the previous research articles to find out the washback effect of task-based assessment of vocabulary on EFL learners. While the diversity of teaching and testing methods within today’s EFL classrooms continues to increase, it is better to pay attention to alternative methods of assessment like task-based vocabulary assessments in contrast to traditional assessment. Despite the existence of many research articles in the field of alternative teaching and assessment methods, Iran's education system has not pay attention to finding an alternative method of assessment that can replace it with its own current unsuccessful traditional method. Therefore, the present paper critically evaluated the previous research articles about the washback effect of task-based assessment of vocabulary on EFL learners. The fundamental motivation for writing the current paper is that Iran's public EFL program suffers from traditional assessment issues. To address these challenges, Iran's assessment system must be changed by employing alternative types of assessment and establishing a teacher assistance program. The first focus of the present paper was to review task-based language teaching (TBLT), task-based language assessment (TBLA), and washback effect definitions. Second, the role of vocabulary in TBLT and TBLA was explained. Next, an overview of the empirical studies on TBLT, TBLA, the washback effect, and vocabulary assessment in international and Iranian contexts was presented. Finally, the research question about the washback effects of task-based vocabulary assessment on EFL learners’ vocabulary learning was answered based on the critical review of the previous empirical research.